THE INFLUENCE OF THE TREASURE HUNT METHOD ASSISTED WITH AUDIO VISUAL MEDIA ON THE LEARNING OUTCOMES OF CLASS V SCIENCES IN SDN 13 PALEMBANG - Vilda Priyanka Jelantik; Dian Nuzulia Armariena; Marleni (Esteem Journal of English Education Study Programme, 2024)
This research was motivated by low student learning outcomes due to students' lack of ability to understand social studies learning material. Apart from that, the learning methods and media used by teachers are less varied, and learning activities by memorizing a very wide range of social studies material make learning seem boring. This research aims to determine the effect of the treasure hunt method assisted by audio-visual media on social studies learning outcomes for class V at SD Negeri 13 Palembang. This research was carried out at SD Negeri 13 Palembang which is located at Jl. Tiger Protection, Bukit Baru, Ilir Barat I District, Palembang City, South Sumatra Province. This research is a type of experimental research, namely the True Experimental Design type. The population and sample in this study were fifth grade students at SD Negeri 13 Palembang, totaling 35 students in the control class and 35 students in the experimental class. Data collection techniques in this research are observation, tests and documentation. Data analysis techniques in this research include Normality Test, Homogeneity Test, Hypothesis Test. The results of this research were hypothesis testing using the t test (Independent Sample t-test), it was found that the sig (2-tailed) value was 0.000 because the significant value was smaller than 0.05, so Ho was rejected and Ha was accepted. It can be concluded that there is an influence of the treasure hunt method assisted by audio-visual media on the social studies learning outcomes for class V at SD Negeri 13 Palembang.